Unextracted cottonseed in diets for monogastric animals. I. The effect of ferrous sulfate and calcium hydroxide in reducing gossypol toxicity - Clawson, AJ; Maner, JH; Gómez G., Guillermo G.; Mejia, O; Flores, Z; Buitrago, J.A. (1975)
Pigs self-fed diets in which whole cottonseed (including the hulls) replaced one third, two thirds or all the protein supplied by soybean meal gained at a reduced rate and mortality resulted at the highest levels. Iron from ferrous sulfate was ineffective in preventing toxicity because of physical problems involved (comminution of the cottonseed and particle size of the crystalline ferrous sulfate) which prevented contact between the iron and the gossypol. Two experiments were conducted using rats to determine the value of calcium hydroxide and ferrous sulfate mixed dry and in solution with unextracted cottonseed meats (dehulled cottonseed) in reducing gossypol toxicity. When the calcium hydroxide was mixed dry with the cottonseed meats, the rats lost weight and the mortality rate was high. Ferrous sulfate mixed dry was effective in preventing mortality but growth rate of rats fed this diet was poor. Performance was greatly improved when either the calcium hydroxide or ferrous sulfate was added to the cottonseed meats in water solution. There was no apparent benefit from adding calcium hydroxide in combination with ferrous sulfate. Rats fed diets containing cottonseed meats (replacing one half the protein supplied by soybean meal) treated with ferrous sulfate solution (800 ppm of iron in the air dry diet) gained faster and required less feed per unit of gain than those fed cottonseed meats treated with calcium hydroxide solution or with a combination of ferrous sulfate and calcium hydroxide. Rats fed the diets containing cottonseed meats treated with ferrous sulfate solution gained at a rate approximately equal to those fed the corn-soybean meal diet.